On the effect of tsunami on nearshore wave energy converters - O'Brien, Laura; Renzi, Emiliano; Dias, Frederic; Christodoulides, Paul (My University, 2012)
With an increasing emphasis on renewable energy resources, wave power technology is fast becoming a realistic solution. The question posed here is whether a nearshore wave energy converter could withstand the force of an incoming tsunami. An analytical 3D model is developed within a linear theory and applied to an array of fixed plates. The time derivative of the velocity potential allows the hydrodynamic force to be found. The hydrostatic force can be found from the difference in free surface heights on either side of the device.
Keywords: Tsunami; Wave power technology